Social Values as One of the Crucial Determinants of Efficient Strategic Management of an Energy Sector Company - Krzysztof Machaczka; Maciej Stopa (Energies, 2022)
A continual increase in the influence of exogenic conditions on a company’s ability to sustain and develop and increasing complexity of the management processes correlated with the discovery of new dimensions of an enterprise, which determine its potential—these all lead to a growing interest in the search for the factors which might facilitate the elevation of the level of integrity of a business model of an enterprise/organisational and managerial system of an enterprise. Currently, it is absolutely necessary to perceive an enterprise not only in the terms of a rational economic system that, in its activity, concentrates on the generation of a positive financial result, and the creation of its value for the stockholders, but also as the system, at the same time, is meant to act responsibly in relation to its stakeholders, society and the market. The observation of successful enterprises shows clearly that the company values make up an element indispensable for the creation of effective strategies of development, and, at the same time, an element guaranteeing them an appropriate level of strategic integrity in external and internal dimensions, paired with the preservation of flexibility for necessary reconfiguration. Some special attention should be paid to the fact that, in order to build permanent competitive advantage, in the context of the strategic dimension of company management, values should play a key role also in the enterprises within heavy industry, including the energy sector. This article aims to present the significance of selected aspects of strategic dimension management in the context of company strategy in one of the largest energy sector companies in Poland. It is based on an analysis of the results of research carried out in the second part of 2021 and at the beginning of 2022. Qualitative studies based on a questionnaire survey and in-depth interviews were conducted among this institution’s managers who are responsible for formulating the company strategy. The study results have shown that social and employees’ personal values, organisational culture, and management by values, have a substantial impact on the character and quality of the strategic dimension management of the analysed company. The article aims to show the role of social values in determining efficiency in the area of managing the strategic dimension of a company. In the context of this aim, the following important research questions should be asked: What is the influence of social values and values represented by the TMT (top management team) on a given company’s efficiency in the context of strategic decisions; and how do these factors influence the stability of the company development, and do they ensure the organisation’s resilience to short-term external changes?